Resolutions of the Financial Education Council as the Subject of Judicial Review - Wegner, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
The subject of this study is the issue of the legal nature of the resolutions of the Financial Education Council containing an addressed to the Financial Ombudsman request about the use of the Financial Education Fund in a specific manner. The resolution has significant legal effects because it binds the Ombudsman in the field of spending the funds. Due to the lack of a detailed regulation devoted to the legislative powers of the Council, the admissibility of judicial review of its resolutions raises doubts.